(untitled) - Baltzan, Paige; Phillips, Amy (Boston, 2009)
Includes bibliographical references and index.; Information systems in business -- Strategic decision making -- Ebusiness -- Ethics and information security -- Enterprise architectures -- Databases and data warehouses -- Networks, telecommunications, and mobile technology -- Operations management and supply chain management -- Customer relationship management and business intelligence -- Enterprise resource planning and collaboration systems -- Systems development and project management -- Globalization, Innovation, and 21st century organizational trends.
Keywords: Industrial management -- Data processing.; Information technology -- Management.; Quản trị công nghiệp -- Xử lý dữ liệu; Công nghệ thông tin -- Quản trị